Memahami "Cultural Studies" dan Multikulturalisme dari Perspektif Pascamodern - Lubis, Akhyar Yusuf (Wacana, Journal of the Humanities of Indonesia, 2004)
Cultural studies is a study of culture, the paradigm of which is quite different from that of the conventional (i.e. modern) studies. If we accept this view, it means that the whole problem of cultural reality, epistemology, and methodology cannot be used to understand and investigate cultural studies and multiculturalism. The infeasibility of using conventional study of culture to apprehend cultural studies and multiculturalism is related with the principle of incommensurability between those two fields, so there are different worldviews and rules (language games) between the two. This difference is vividly showed in character and model of study that conceives culture as homogeneity, single identity, patterned values, fragmented. Cultural studies and multiculturalism conceive culture as plurality, complexity, constructed identity, dynamics, diversity, interaction, and something porous. In light of this worldview, cultural studies, multiculturalism, and globalism, according to my analysis, must be understood and studied from postmodern perspective or paradigm.